Assessment of Physical Activity of Patients With Chronic Pain. (June 2014) - Perruchoud, Christophe; Buchser, Eric; Johanek, Lisa M.; Aminian, Kamiar; Paraschiv‐Ionescu, Anisoara; Taylor, Rod S.
Abstract : Objectives: To define the key terms and concepts relating physical activity to chronic pain; to provide a brief overview of the various methods of assessment of physical activity; to review the current literature about physical activity and chronic pain; and to identify needs for future research. Materials and Methods: A narrative review based on results of a PubMed search (to May 2011) and the references of recent systematic reviews. Results: Many methods exist for measuring physical activity. Movement sensors, such as accelerometers, offer objective assessment of physical activity of patients with chronic pain. It is often assumed that patients who feel disabled and report daily life restrictions due to chronic pain also will be less physically active. Studies that have compared the activity of patients with chronic back pain with that of healthy individuals consistently showed that the relationship of physical activity and severity of pain, as well as the change in activity following interventions, was variable and complex. Conclusions: It is important to understand the relationship between physical activity and chronic pain. Future studies should objectively assess not only the pattern and complexity of that relationship but also the interaction with the patient's mood and ability to cope with the pain.